BCG Vaccine Derived Peptides Induce SARS-CoV-2 T Cell Cross-Reactivity - Eggenhuizen, Peter J.; Ng, Boaz H.; Chang, Janet; Fell, Ashleigh L.; Cheong, Rachel M. Y.; Wong, Wey Y.; Gan, Poh-Yi; Holdsworth, Stephen R.; Ooi, Joshua D. (Frontiers in Immunology, 2021)
Epidemiological studies and clinical trials suggest Bacillus Calmette-Guérin (BCG) vaccine has protective effects against coronavirus disease 2019 (COVID-19). There are now over 30 clinical trials evaluating if BCG vaccination can prevent or reduce the severity of COVID-19. However, the mechanism by which BCG vaccination can induce severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-specific T cell responses is unknown. Here, we identify 8 novel BCG-derived peptides with significant sequence homology to either SARS-CoV-2 NSP3 or NSP13-derived peptides. Using an in vitro co-culture system, we show that human CD4+ and CD8+ T cells primed with a BCG-derived peptide developed enhanced reactivity to its corresponding homologous SARS-CoV-2-derived peptide. As expected, HLA differences between individuals meant that not all persons developed immunogenic responses to all 8 BCG-derived peptides. Nevertheless, all of the 20 individuals that were primed with BCG-derived peptides developed enhanced T cell reactivity to at least 7 of 8 SARS-CoV-2-derived peptides. These findings provide an in vitro mechanism that may account, in part, for the epidemiologic observation that BCG vaccination confers some protection from COVID-19.